Pedro Boza (1660-1715) : au service de la justice dans la sierra zapotèque du Mexique - Thomas Calvo (Les Cahiers de Framespa)
“The Commonwealth cannot be held with threads”, Churchill would have said. In his own way, the existence of Pedro Boza, who lived on the margins of the Spanish Monarchy, in the problematic province of Villa Alta also demonstrates this. He was a tiny cog in the great colonial machine, at best the teniente general of the governor (alcalde mayor). In this microcosm he played on all sides, sometimes on the side of the established authority, sometimes in the service of a few caciques who were searching their own fortune. Boza always defended his interests. And how about those of the Monarchy? Towards the end of his life, as a simple witness of assistance, apparently without any power, he was able to take advantage of the circumstances, to become indispensable in the judicial mechanisms, acting simultaneously as clerk and quasi-judge. In this way he helped to normalize the life of the province. It was an immaterial, but very real, authority at ground level.